Predictive Factors of Intensive Care Unit Readmission among Older Patients: A Retrospective Study. - Sunhui Choi; Kuem Sun Han; Sung Reul Kim; Hyemin Lim (Korean Journal of Adult Nursing, 2025)
Purpose: This study aimed to determine the rates of intensive care unit readmission and to identify the factors influencing readmission among intensive care unit patients aged≥65 years with internal medicine conditions. Methods: We retrospectively reviewed electronic medical records from a tertiary care hospital in Seoul, analyzing the characteristics of patients who were and were not readmitted between December 2020 and September 2022. Results: A total of 351 patients were included. The unplanned intensive care unit readmission rate was 4.8% within 7 days and 9.1% beyond 7 days after discharge. Comorbid diabetes, higher total bilirubin levels at intensive care unit admission, lower PaO2/FiO2 ratios at discharge, and elevated Blood Urea Nitrogen (BUN) levels at discharge were associated with an increased risk of readmission within 7 days. In contrast, hypertension, prolonged intensive care unit stays, and lower hemoglobin levels at discharge were associated with readmissions occurring after 7 days. Conclusion: Intensive care unit readmission among older patients is influenced by several clinical and hematological factors. Nurses should consider a patient's history of diabetes and hypertension, length of intensive care unit stay, and laboratory values-specifically total bilirubin at admission, and PaO2/FiO2 ratio, hemoglobin, and BUN levels at discharge-when making discharge decisions. These findings can inform the development of discharge guidelines.